Inhibition of a type III secretion system by the deletion of a short loop in one of its membrane proteins. (1st May 2013) - Meshcheryakov, Vladimir A.; Kitao, Akio; Matsunami, Hideyuki; Samatey, Fadel A.
<x xml:space="preserve">Abstract</x> The membrane protein FlhB is a highly conserved component of the flagellar secretion system. It is composed of an N‐terminal transmembrane domain and a C‐terminal cytoplasmic domain (FlhBC). Here, the crystal structures of FlhBC from Salmonella typhimurium and Aquifex aeolicus are described at 2.45 and 2.55 Å resolution, respectively. These flagellar FlhBC structures are similar to those of paralogues from the needle type III secretion system, with the major difference being in a linker that connects the transmembrane and cytoplasmic domains of FlhB. It was found that deletion of a short flexible loop in a globular part of Salmonella FlhBC leads to complete inhibition of secretion by the flagellar secretion system. Molecular‐dynamics calculations demonstrate that the linker region is the most flexible part of FlhBC and that the deletion of the loop reduces this flexibility. These results are in good agreement with previous studies showing the importance of the linker in the function of FlhB and provide new insight into the relationship between the different parts of the FlhBC molecule.